Changes in the Proliferation Rate, Clonogenicity, and Radiosensitivity of Cultured Cells During and After Continuous Low-Dose-Rate Irradiation - Zhen Wang; Chikao Sugie; Masahiro Nakashima; Takuhito Kondo; Hiromitsu Iwata; Takahiro Tsuchiya; Yuta Shibamoto (SAGE Publishing, 2019)
We investigated the effects of continuous low-dose radiation on proliferation, clonogenicity, radiosensitivity, and repair of DNA double-strand breaks (DSBs) in human salivary gland (HSG) tumor cells. Human salivary gland cells were cultured on acrylic boards above very-low-dose (4.3 μSv/h) or low-dose (27 μSv/h) radiation-emitting sheets or without sheets. Total cell numbers and plating efficiencies were compared among the 3 groups every 1 or 2 weeks until 6 weeks after starting culture. At 2, 4, and 6 weeks, surviving fractions of HSG cells after irradiation at 2 to 8 Gy cultured on the very-low-dose or low-dose sheets were compared to those of the control. At 4 weeks, HSG cells irradiated at 2 Gy were assessed for phosphorylated histone (γH2AX) foci formation, and DSBs were evaluated. No significant differences were observed in total cell number or plating efficiencies with or without low-dose-emitting sheets. The surviving fractions after irradiation of the very-low-dose group at 2 to 6 weeks and those of the low-dose group at 2 to 4 weeks were higher than those of the control ( P < .01). Thus, a radioadaptive response was clearly demonstrated. From the γH2AX foci quantification, the adaptive responses were considered to be associated with the efficient repair of DSB, especially slow repair, in this cell line.